FAKTOR PENENTU PERMINTAAN TENAGA KERJA DI PROVINSI DKI JAKARTA - Adhitya Vega Darmawan; Hermien Triyowati (Media Ekonomi, 2016)
The purpose of this research was to analyzed labor demand in DKI Jakarta. Independent variables that used in this research are GRDP, investment, and wages). While the dependent variable is labor absorption.  Some data that were required in this research included the number of labors, data of GRDP, data of investment, and also wages of DKI Jakarta which received from BPS of DKI Jakarta. The data were analyzed by the Error Correction Model (ECM)  The result of this research showed that GRDP, investment, and wages had the same influence to labor demand DKI Jakarta. Partially, GRDP had positive and significant influence labor demand in DKI Jakarta. In other hand,  wages had a negative and significant influence to labor demand in DKI Jakarta. While investment has no significant effect on labor demand in DKI Jakarta. The influence of GRDP, investment, and wages to labor demand in DKI Jakarta had percentage is 87,39%. While 12,61% was explained by another factor.